English medium instruction and the English language practitioner - Galloway, N; Rose, H (Oxford University Press, 2021)
The paper explores the impact of the growth in English medium instruction (EMI) on the field of ELT. Increasing studies report students’ language-related challenges and linguistic preparedness to be major barriers to successful implementation of EMI. These challenges, which have accompanied an unfettered growth in EMI provision, impact on practitioners and students and highlight the role of ELT practitioners in providing language support. This paper outlines how EMI is changing the role of ELT practitioners in the internationalized and ‘Englishized’ higher education sector, who increasingly teach on EAP programmes. EMI research is in a relative stage of infancy, yet a growing body of evidence highlights the importance of academic and language support. Drawing on evidence from recent research, we explore the integral role that ELT instructors have in helping students with their content learning, and make suggestions to facilitate greater integration of ELT within EMI contexts.